Effects of pre-sowing treatments on seed germination and seedling growth of Glycine max(L.) Merrill - Okoh, Thomas; Okekporo, Efe Stephen; Onoja, Charity Elahi (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study assessed the effects of some pre-sowing seed treatments on seed germination and seedling growth rate of three varieties of Glycine max– TGX 1935-3F (variety 1), TGX 1448-2E (variety 2) and TGX 1951-3F (variety 3). The treatments included four different concentrations of sulphuric acid (0.1, 0.2, 0.3, 0.6mole/dm3) termed T1, T2, T3 and T4 respectively, for five minutes and three hot water temperature variations (40, 60, and 800C) termed T5, T6 and T7 respectively, for twenty minutes. Germination was monitored as emergence of radicle and plant growth parameters were also measured. Treatments T4 (93.33%, 86.67%, 96.67%) and T7 (90.00%, 83.33%, 93.33%) had the highest germination percentages in the three varieties. Plant height in T2, T3 and T4was significantly different (p< 0.05) from the control in all acid pre-treatments for all varieties; for hot water pre-treatment, plant height in varieties 1 and 3 were significantly (p< 0.05)different from the control in all treatments. Furthermore, T6 and T7 (variety 2) were also significantly different from the control. Number of leaves showed significant difference from the control in T3, T4 (variety 1), T4 (variety 2), and T2, T3, and T4 respectively. Additionally, T5, T6 and T7 were significantly different from the control in varieties 1 and 2. Leaf area was significantly different (p< 0.05)from the control in T1, T2, T3, T4 (varieties 1 and 3), and in T4 (variety 2). Moreover, T5, T6 and T7 were significantly different from the control in varieties 1 and 3, and in T7 in variety 2. Number of buds was significantly different (p< 0.05) in T2, T4 (variety 1), and in T3 and T4 in variety 3. There was also significant difference in the number of buds in T5, T6 and T7 in variety 3. The results suggested treatments T4 and T7 had the best overall effect on germination and overall growth, and hence hereby recommended.